INDEPENDENT CURRICULUM IN THE DEVELOPMENT OF MARGINALIZED COMMUNITIES AT MASTER (MASJID TERMINAL) INDONESIA HIGHT SCHOOL DEPOK WEST JAVA - Syarifah, Syarifah; Azizah, Nurul; Umami, Halida; Mufidah, Zuhrotul; Dhiya Ulhaq, Syifa (FORPIM PTKIS ZONA TAPAL KUDA, 2025)
Teachers must play a strategic role in leading the next generation, particularly those from marginalized groups who are frequently denied access to education, as a result of the transformation of education in the period of Industrial Revolution 4.0. In order to address the educational requirements of marginalized populations like the unemployed, low-income families, and children from broken homes, the Master Indonesia School in Depok, West Java, implemented the Independent Curriculum. This study focuses on this implementation. Observation, interviews, and documentation techniques are used in this qualitative, descriptive study. The Miles and Huberman model (data reduction, data presentation, and conclusion drawing) is used in data analysis. The findings demonstrate how the Master School adapted the Independent Curriculum by fusing it with contextual learning ideas and components of the 2013 Curriculum. Religious programs like Al-Quran Reading Guidance (BBQ) and corpse care protocols, as well as nonreligious skill training in areas like online commerce, automotive, graphic design, screen printing, and theater, supplement the learning activities. A student-potential-based strategy and an autonomous learning curriculum are essential for empowering students from underrepresented groups.